In the age of the teaching artist? What teaching artists are and do - Ulvund, Marit (Nordic Journal of Art & Research, 2015)
The term teaching artist and the concept of teaching artistry developed in the USA in the 1970s, originating from artists performing this kind of work in New York City. Other terms, such as artist-teacher, creative agent, community artist, and others, are in use around the world. In Norway, the English term is often used; however, this author suggests the use of the Norwegian word “kunstnerlærer”. The review of recent research and literature, and observations of practice, recognizes the teaching artist as a professional artist working in and through the arts in an educational or community setting. Research in the practice field demonstrates that the teaching artist in programs and partnerships represent a new and effectual model for arts in education and community work, and a model acknowleding this is presented and discussed. The two first international teaching artist conferences (Oslo 2012, Brisbane 2014) confirm that a world community of teaching artists is emerging. However, the field has received relatively little attention from researchers, and the scholarship that does exist is limited to work in only a few countries. Coupled with the efficacy of the model, this study finds that there is a strong need for further exploration of ongoing and successful teaching artist practices, as well as a need for developing theory and concepts related to the competence needed by teaching artists. This article outlines a framework for teaching artistry and a definition of the teaching artist. In the context of the contemporary Norwegian arts and culture sector, the large potential in expanding teaching artistry practice are underscored.